2021
DOI: 10.1101/2021.03.16.435601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cluster Analysis of SARS-CoV-2 Gene using Deep Learning Autoencoder: Gene Profiling for Mutations and Transitions

Abstract: We report on a method for analyzing the variant of coronavirus genes using autoencoder. Since coronaviruses have mutated rapidly and generated a large number of genotypes, an appropriate method for understanding the entire population is required. The method using autoencoder meets this requirement and is suitable for understanding how and when the variants emarge and disappear. For the over 30,000 SARS-CoV-2 ORF1ab gene sequences sampled globally from December 2019 to February 2021, we were able to represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies have reported the correlation between phylogenetic relationships in genomic data and projections by dimensionality reduction algorithms, such as PCA (Alexe et al 2008;Miyake et al 2021). Those studies suggest that LAEs can learn phylogenetic relationships from genomic data that can be clustered based on mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the correlation between phylogenetic relationships in genomic data and projections by dimensionality reduction algorithms, such as PCA (Alexe et al 2008;Miyake et al 2021). Those studies suggest that LAEs can learn phylogenetic relationships from genomic data that can be clustered based on mutations.…”
Section: Discussionmentioning
confidence: 99%